Pengaruh Efisiensi Modal Kerja Terhadap Profitabilitas pada Perusahaan Sub Sektor Otomotif dan Komponennya yang Terdaftar di ISSI - Rella Asri Utami; Novi Mubyarto; Mohammad Orinaldi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This thesis aims to determine and analyze the simultaneous influence of cash turnover, accounts receivable turnover, and inventory turnover on the profitability of automotive sub-sector companies and their components listed on the Indonesian Sharia Stock Index for the period 2019-2023. As well as to determine and analyze the partial influence of cash turnover, accounts receivable turnover, and inventory turnover on the profitability of automotive sub-sector companies and their components listed on the Indonesian Sharia Stock Index for the period 2019-2023. This study uses a quantitative approach with secondary data, using panel data regression analysis tools. The results of the conclusions are as follows: 1) The estimation results show that simultaneously the cash turnover, receivables turnover, and inventory turnover variables together have a positive and significant effect on the profitability of automotive sub-sector companies and their components listed on the Indonesian Sharia Stock Index for the 2019-2023 period. 2) The estimation results show that partially the cash turnover variable has a positive and significant effect on the profitability of automotive sub-sector companies and their components listed on the Indonesian Sharia Stock Index for the 2019-2023 period. The receivables turnover variable has a positive and significant effect on the profitability of automotive sub-sector companies and their components listed on the Indonesian Sharia Stock Index for the 2019-2023 period, and the cash turnover variable has a positive and significant effect on the profitability of automotive sub-sector companies and their components listed on the Indonesian Sharia Stock Index for the 2019-2023 period.